Determining pull-out strength for screws engaging posterior cortex, compared to screws placed into the tibia metaphysis for medial malleolus ankle fractures. A comparative cadaver model - Conradie, Gerhard Petrus (University of the Free State, 2018)
Aim: Failure of fixation of an ankle fracture is common in bone of poor quality. Improving the strength of fixation could lead to better results. The aim of this study is to evaluate if the pullout strength of a medial malleolus screw can be increased if it is inserted in such a way that the screw engages the posterior metaphyseal cortex of the tibia. Method: Comparative study on 13 cadavers, fixing a medial malleolus osteotomy with a 4.0mm partial threaded cancellous screw. The right ankle of each cadaver was fixed with a screw engaging the posterior metaphysical cortex, the left ankle was fixed with a screw only engaging the trabecular metaphyseal bone. Axial traction was applied to the screw until failure of fixation occurred. Failure being defined as 2mm distraction over the fracture site. Axial traction was applied with a traction scale calibrated in kilograms. Results: In all ankle osteotomies an anatomic reduction was achieved. The mean strength was 87.66N for metaphysical purchase screws, compared to 208.88N for cortical Purchase screws. (p-value 0.002). For screws inserted not engaging the posterior cortex of the tibia, the lowest recorded pullout strength was 15.69N. The maximum recorded pullout strength, for a screw not engaging the cortex, was 181.42N. For screws engaging the posterior tibia cortex the minimum recorded pullout strength was 72.57N and the maximum recorded 414.82N. Conclusion: The results show a significant improvement in the pullout strength of medial malleolus screws inserted to engage the posterior tibia cortex.
Keywords: Cadaver; Pull-out strength; Non-union; Mal-union; Ankle; Fracture; Dissertation (M.Med. (Orthopaedic Surgery)--Univesity of the Free State, 2018; Medial malleolus